2021
DOI: 10.3390/ijerph182111450
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Its Impact on Families’ Mental Health: The Role Played by Parenting Stress, Parents’ Past Trauma, and Resilience

Abstract: International research has evidenced the psychological impact of the COVID-19 pandemic on families, and the key role played by parenting stress levels. Although significant associations with parents’ past trauma and resilience have been shown, this study aimed to explore their complex interplay on the relationship between parents’ peritraumatic distress due to COVID-19, parenting stress, and children’s psychopathological difficulties. We recruited 353 parents with children aged two to 16 years via an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 84 publications
6
35
0
Order By: Relevance
“…That said, based on previous research (e.g., Cusinato et al, 2020 ; Laufer & Bitton, 2021 ; Romero et al, 2020 ) it is likely that parents’ resilience helped to mitigate the impacts of COVID-19-related psychological stressors. This finding is in line with previous work conducted on parents ( n = 353; M age = 42.15; 64% female) in Italy by Marzilli et al (2021) who investigated resilience, stress, and mental health of parents of school-aged children (M age = 9.28). The authors reported that parents’ distress due to COVID-19 was significantly and negatively associated with their resilience ( r = −0.27, p < .01; Marzilli et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That said, based on previous research (e.g., Cusinato et al, 2020 ; Laufer & Bitton, 2021 ; Romero et al, 2020 ) it is likely that parents’ resilience helped to mitigate the impacts of COVID-19-related psychological stressors. This finding is in line with previous work conducted on parents ( n = 353; M age = 42.15; 64% female) in Italy by Marzilli et al (2021) who investigated resilience, stress, and mental health of parents of school-aged children (M age = 9.28). The authors reported that parents’ distress due to COVID-19 was significantly and negatively associated with their resilience ( r = −0.27, p < .01; Marzilli et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with previous work conducted on parents ( n = 353; M age = 42.15; 64% female) in Italy by Marzilli et al (2021) who investigated resilience, stress, and mental health of parents of school-aged children (M age = 9.28). The authors reported that parents’ distress due to COVID-19 was significantly and negatively associated with their resilience ( r = −0.27, p < .01; Marzilli et al, 2021 ). Similar findings were noted in Lim et al (2021) Singapore-based study exploring factors affecting parents’ psychological distress throughout the pandemic ( n = 107; 80.4% female).…”
Section: Discussionsupporting
confidence: 92%
“…Four hundred mothers and their children were selected from a larger previous study (Marzilli et al, 2021 ) started before the COVID-19 outbreak (in October 2019; T1) and re-contacted during the first wave of the pandemic (March 2020; T2), and in October 2021 (T3). The recruitment of the subjects for this research was based on consecutive sampling of individuals who (in the previous study) declared their availability to be re-contacted for other studies.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies of other pandemics have also shown that resilience plays a key role in mitigating the negative effects of stress on parents. Recent studies further point in this direction in the context of the COVID-19 pandemic [ 22 ]. Although data on youths are starting to be published, relevant data from France on this topic are lacking.…”
Section: Introductionmentioning
confidence: 99%